2021
DOI: 10.1186/s12958-021-00823-z
|View full text |Cite
|
Sign up to set email alerts
|

TRIB3 regulates FSHR expression in human granulosa cells under high levels of free fatty acids

Abstract: Background Granulosa cells (GCs) in cumulus oophorus highly express follicle stimulating hormone receptor (FSHR), which is the most important mediator of both estradiol synthesis and oocyte maturation. Obese women have elevated free fatty acids (FFAs) levels in their follicular fluids and decreased FSHR expression in GCs, which is related to an altered protein kinase B/glycogen synthase kinase 3β (Akt/GSK3β) signaling pathway. Such FFA increases accompany 3-fold rises in pseudokinase 3 (TRIB3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Following overnight culture for 24 h, the cells grew well and were adherent. FSHR is a marker of human ovarian GCs ( 26 ). As shown by immunofluorescence staining ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Following overnight culture for 24 h, the cells grew well and were adherent. FSHR is a marker of human ovarian GCs ( 26 ). As shown by immunofluorescence staining ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, studies have shown that elevated E2 levels lead to decreased levels of follicle-stimulating hormone (FSH) due to negative feedback from the pituitary gland [52,53]. Recent studies have shown that elevated FSH levels are an important factor in the development of Alzheimer's disease in menopausal women [54]. Moreover, FSHR knockout mice showed significant depression and affective disorders [55,56].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have shown that elevated E2 levels lead to decreased levels of follicle-stimulating hormone (FSH) due to negative feedback from the pituitary gland [43,44]. Recent studies have shown that elevated FSH levels are an important factor in the development of Alzheimer's disease in menopausal women [45]. Moreover, FSHR knockout mice showed signi cant depression and affective disorders [46][47][48].…”
Section: Discussionmentioning
confidence: 99%